IMPLEMENTASI INFORMATION AND COMMUNICATION TECHNOLOGIES (ITC) DALAM PEMBELAJARAN DI KURIKULUM MERDEKA - Tomasoa, Yellia; Simal, Rufiati; Mautang, Hizkia Gymnastic; Latupeirissa, Louvenska N; Apituley, Vicktor Henry Rony (German für Gesellschaft (J-Gefüge), 2025)
The implementation of Information and Communication Tecnologies (ITC) or better known as information and communication technology (ICT) in learning in primary schools is becoming increasingly important along with the rapid development of science and technology The geographical condition of Dobo, which is a 3T area (frontier, outermost, underdeveloped), adds complexity to the implementation of ICT in primary schools. Limited infrastructure and accessibility are major barriers to the implementation of this technology. However, with the rapid advancement of technology, it is important for schools in 3T areas to keep trying to integrate ICT in the learning process. This is in line with research findings showing that the use of ICT can assist in the development of learning media, guidance services, language learning, and online library services. The purpose of this community service activity (PkM) is to implement Information Communication and Tecnologies (ITC) or ICT in learning at SD Inpres Rabiajala, so as to improve the quality of education in 3T areas. With the training and socialisation to teachers, it is expected to create a learning environment that supports the effective use of ICT.